2019
DOI: 10.1093/nar/gkz1120
|View full text |Cite
|
Sign up to set email alerts
|

Different class IIa HDACs repressive complexes regulate specific epigenetic responses related to cell survival in leiomyosarcoma cells

Abstract: Transcriptional networks supervising class IIa HDAC expression are poorly defined. Here we demonstrate that MEF2D is the key factor controlling HDAC9 transcription. This control, which is part of a negative feed-back loop during muscle differentiation, is hijacked in cancer. In leiomyosarcomas the MEF2D/HDAC9 vicious circuit sustains proliferation and cell survival, through the repression of the death receptor FAS. Comprehensive genome-wide studies demonstrate that HDAC4 and HDAC9 control different genetic pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(66 citation statements)
references
References 68 publications
3
59
0
Order By: Relevance
“…Moreover, experimental variations and the discordance of species-related biorthogonal specificity might also be introduced in COGC-seq, which would affect subsequent data interpretation. Therefore, two statistical ChIP-seq normalization approaches, MAnorm and DiffBind, which were extensively used in recent studies 57 59 , were employed to detect genomic regions showing differential quantitative OCP binding. The genotoxicity-induced differential binding regions determined by MAnorm and DiffBind were of a similar magnitude and highly coincident, reflecting the reliability of the results.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, experimental variations and the discordance of species-related biorthogonal specificity might also be introduced in COGC-seq, which would affect subsequent data interpretation. Therefore, two statistical ChIP-seq normalization approaches, MAnorm and DiffBind, which were extensively used in recent studies 57 59 , were employed to detect genomic regions showing differential quantitative OCP binding. The genotoxicity-induced differential binding regions determined by MAnorm and DiffBind were of a similar magnitude and highly coincident, reflecting the reliability of the results.…”
Section: Discussionmentioning
confidence: 99%
“…We found that MITR occupied region was enriched around the TSS region ( Figure 6 A and 6 B ). Giorgio et al had analyzed HDAC9 ChIP sequencing and found that distal intergenic regions occupied more than 70% of all the peaks 37 . We also found that the main components of peaks in MITR ChIP-seq were in intergenic and intron regions ( Figure 6 C ), suggesting that MITR might also occupy the distal regulative elements.…”
Section: Resultsmentioning
confidence: 99%
“…Kong et al proposed that the intron domain of IL6 could recruit the HDAC-MEF2 repressive complex, which suppressed the pro-inframammary target gene, thereby enhancing chronic infections and cancer 42 . Giorgio et al demonstrated that regions recognized by MEF2D/HDAC4/HDAC9 repressive complexes demonstrated associations as active enhancers for tumor growth, and many of them were bonded both by MEF2s and HDACs 37 . In our study, we confirmed that MEF2A could directly bind to and suppress IL11.…”
Section: Discussionmentioning
confidence: 99%
“…While studies are increasingly describing RIS epigenetics, detailed data about the epigenetic modifications in other types of OIS are unavailable. Additional data are desirable since increasing evidences highlight the key roles played by epigenetic regulators in maintaining OIS and counteracting oncogenic transformation [84,[111][112][113][114][115][116]. For example, in melanomas the activation of H3K9me3 demethylases (LSD1 and JMJD2C) selectively de-represses E2F target genes, allowing senescence escape and tumorigenesis [117].…”
Section: Different Types Of Ois?mentioning
confidence: 99%
“…The chromatin remodeling observed in different senescence models seems to represent a temporal and spatial evolution of what is observed after a short-time treatment of the cells with DNA damaging agents. Although it is clear that an altered epigenome can expose cells to DSBs [134] and that epigenetic regulators control the fate of damaged cells [15,55,66,115,[178][179][180], investigations on the epigenetic inheritance in daughter cells coming from DNA-damaged cells are still in their infancy [177].…”
Section: Final Considerations: the Link Between Senescence Aging Epmentioning
confidence: 99%